(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Motivation is the factor that motivates each individual to try and strive to perform the tasks to achieve the goals. For medical facilities, the working motivation of medical staff affects the quality of medical service delivery. Objective: Analyzing some related factors to the working motivation of health workers at Hai Ba Trung District Health Center Hanoi Capital in 2022. Methods: Cross-sectional study, quantitative research. Results and conclusion: From the analysis of quantitative information of 339 health workers at Hai Ba Trung District Health Center through questionnaires, the research results show that the working motivation of health workers at Hai Ba Trung District Health Center is high (76,8%). Some factors related to working motivation are age, working duration, and monthy income of health workers (p<0.05). Regression equation relating between 8 groups of factors with the general working motivation of health workers: DLC = 0,203 + 0,184*B + 0,111*C + 0,131*D + 0,072*E + 0,254*G + 0,238*H + 0,245*K - 0,038F.